Equation of state for aqueous electrolyte systems based on the semirestricted non-primitive mean spherical approximation - Herzog, Stefanie; Gross, Joachim; Arlt, Wolfgang (Fluid Phase Equilibria, 2010)
The semirestricted non-primitive mean spherical approximation (npmsa) is used in combination with the PC-SAFT equation of state to model completely dissociating aqueous alkali halide systems. The salts are described using ion-specific parameters from tables and correlations. Upon analyzing aqueous electrolyte systems at infinite dilution of the salt it was concluded that for the arithmetic mean ion diameter of anion and cation, the semirestricted npmsa contribution gives no reliable results. Therefore, this parameter is adjusted in this work. The model was applied to aqueous alkali halide systems up to the solubility limit at T = 298.15K. Mean ionic activity coefficients and osmotic coefficients were correlated with good results. The model was subsequently applied to temperatures up to T = 373.15K and compared to liquid densities and to system pressures up to the solubility limit of the salts in water. The agreement between experimental data and the proposed equation of state is satisfactory for the liquid densities and excellent in case of the system pressures. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Aqueous electrolyte systems; Semirestricted non-primitive mean; spherical approximation (npmsa); PC-SAFT equation of state